2020
DOI: 10.1016/j.ijpddr.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Nullscript inhibits Cryptosporidium and Toxoplasma growth

Abstract: Cryptosporidium and Toxoplasma are parasites that have caused problems worldwide. Cryptosporidium causes severe watery diarrhoea and may be fatal in immunocompromised patients and in infants. Nitazoxanide is the only agent currently approved by the FDA, but its efficacy is limited. Toxoplasmosis is also a problem in the immunocompromised, as currently available treatment options have limited efficacy and patient tolerance can be poor. In the present inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Very little is known about epigenetic regulation in Cryptosporidium , but the C . parvum genome encodes histone modification enzymes [ 64 ], and the parasites are susceptible to pharmacological inhibition of these pathways [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about epigenetic regulation in Cryptosporidium , but the C . parvum genome encodes histone modification enzymes [ 64 ], and the parasites are susceptible to pharmacological inhibition of these pathways [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nitazoxanide was used as a standard comparative drug. In vitro inhibition assays were carried out as previously described [22,23]. Briefly, oocysts were suspended in 1 ml of 0.1% sodium hypochlorite in PBS, incubated for 5 min at 4˚C, centrifuged for 10 min at 3000 rpm, and washed three times in PBS.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…As for the treatment of C. parvum infection, it does not have an effective treatment directly, except for (NTZ) Nitazoxanide which is proven by the World Health Organization, but it is not effective for people with immunodeficiency, and many anti-Cryptosporidiosis compounds have been used, but they did not give positive results. Effective and did not kill the Oocyst permanently in a record time, including Metronidazole, Azithromycin, Paromomycin [7] ISSN: 2583-4053 Volume-1 Issue- From recent studies, Nullscript was identified as a compound that has a growth inhibitory effect, and was less toxic to host cells, Nullscript was able to significantly reduce the release of Oocyst in mice infected with C. parvum [8]…”
Section: Introductionmentioning
confidence: 99%